Occurrence of Demodex infestation in chronic blepharitis in a tertiary care hospital in North-East India - Hazarika, Suranjana C.; Hazarika, Himanto N.; Ghuge, Ashwini (International Journal Of Community Medicine And Public Health, 2021)
Background: Chronic blepharitis is frequently encountered by ophthalmologists. Demodex mites (Demodex folliculorum and Demodex brevis) can play a role in its pathogenesis, especially in treatment-resistant cases. Demodex infestation often remains underdiagnosed and undertreated. Definitive diagnosis can be made with lash-sampling. Objective of the study was to find the association between Demodex infestation and chronic blepharitis. Methods: The study included 80 patients diagnosed with chronic blepharitis and 80 controls without blepharitis. Four eyelashes were epilated from each lower and upper lids of the right and left eye (a total of sixteen samples) of each participant. Eyelash samples were examined under a light microscope and Demodex species were identified and counted. Results: Demodex mites were detected in 45 cases (56.25%) and 14 controls (17.5%). Significant association was found between demodex infestation and blepharitis as odd’s ratio was found to be 6.0612 and p value <0.0001. D. folliculorum was detected in 42 cases, D. brevis in 2 cases while in one case, both were detected. The mean age for Demodex positive cases and controls were 49.78±13.25 and 64±7.86 years, respectively. Amongst the cases, Demodex was detected in 57.69% males (30 out of 52) and 53.55% females (15 out of 28). Conclusions: There is significant co-relation between Demodex infestation and chronic blepharitis. Demodex infestation should be part of the differential diagnosis of chronic blepharitis.